Political cartoons in the first decade of the millennium - Sani, Iro; Abdullah, Mardziah Hayati; Mohamad Ali, Afida; Abdullah, Faiz Sathi (Universiti Putra Malaysia Press, 2014)
The beginning of the new millennium (the year 2000 to 2010) has witnessed a dramatic increase in the political cartoons’ research. By their nature, political cartoons constitute a specific genre of political reporting in that they are pictorial representations which depict political and social issues and events, as well as the parties involved, in an immediate and condensed form. The genre is characterised by humorous depiction of events, exploiting the ability of irony and satire to unravel, ridicule and attack in a playful, witty and artful fashion (Test, 1991). They project a particular point of view (El Refaie, 2009) and enlighten readers on public issues while exposing wrong practices (Akande, 2002). Due to the increasing research on political cartoons, this study reviews previous studies conducted in the area from the beginning of the millennium (2000) to the year 2010 that marks the first decade of the 21st century millennium. It is hoped that the review will highlight how the genre contributes to social and political commentary and to provide an inspiration for further research in political cartoons.